Czy "młodość musi się wyszumieć"? O wartościowaniu młodzieży w polskiej frazeologii = "Młodość musi się wyszumieć"? The valuation of youth in Polish phraseology - Nikołajczuk, Krystyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article is devoted to the analysis of the valuation of youth in Polish phraseology. It includes not only the systemic connotations (dictionary definitions) of idioms, but also contextual connotations. The peculiarities of the use of selected idioms in NKJP and Internet (frequency, innovations) have been also presented in the article.
Keywords: frazeologia; młodość; konotacje systemowe i kontekstowe; nacechowanie pejoratywne i melioratywne; phraseology; youth; aspects of meaning; systemic and contextual connotations; pejorative and ameliorative values